👤

Pahelp. Pre-Cal po. Tysm.​

Pahelp PreCal Po Tysm class=

Sagot :

Problem 1:

Equation of an ellipse is:

[tex]\[\frac{{{{(x - h)}^2}}}{a^2} + \frac{{{{(y - k)}^2}}}{b^2} = 1\][/tex]

[tex]\[\begin{array}{l}4{x^2} + {y^2} - 8x + 4y + 4 = 0\\4{x^2} - 8x + {y^2} + 4y + 4 = 0\\4({x^2} - 2x + {1^2}) + ({y^2} + 4y + {2^2}) = - 4 + 4({1^2}) + {2^2}\\4{(x - 1)^2} + {(y + 2)^2} = - 4 + 4 + 4\\4{(x - 1)^2} + {(y + 2)^2} = 4\\{(x - 1)^2} + \frac{{{{(y + 2)}^2}}}{4} = 1\end{array}\][/tex]

Problem  2:

[tex]\[\begin{array}{l}21{x^2} - 4{y^2} + 84x - 24y = 36\\21{x^2} + 84x - 4{y^2} - 24y = 36\\21({x^2} + 4x + {2^2}) - 4({y^2} + 6y + {3^2}) = 36 + 21({2^2}) - 4({3^2})\\21{(x + 2)^2} - 4{(y + 3)^2} = 36 + 84 - 36\\21{(x + 2)^2} - 4{(y + 3)^2} = 84\\\frac{{{{(x + 2)}^2}}}{4} - \frac{{{{(y + 3)}^2}}}{{21}} = 1\end{array}\][/tex]

The equation formed is a hyperbola

[tex]\[\frac{{{{(x - h)}^2}}}{a^2} - \frac{{{{(y - k)}^2}}}{b^2} = 1\][/tex]

c²= a² + b²

c² = 4 + 21

c² = 25

c = √25

c = 5

Center(h, k)

Center(-2, -3)

Focus(h + c, k), (h - c, k)

Focus(-2 + 5, -3), (-2 - 5, -3)

Focus(3, -3), (-7, -3)

Co-vertices(h, b - k), (h, b + k)

Co-vertices(-2, √21 - 3), (-2, - √21 - 3)

Co-vertices(-2, 1.58257569), (-2, -7.58257569)

Equation for Circle 1

where Focus(3, -3) of a hyperbola is the center of a circle

Center(3, -3) and passes through the farther vertex of a hyperbola (-2, 1.583)

get the radius of the circle by applying the distance formula

[tex]\[\begin{array}{l}r = \sqrt {{{({x_2} - {x_1})}^2} + {{({y_2} - {y_1})}^2}} \\\\r = \sqrt {{{( - 2 - 3)}^2} + {{(1.583 - ( - 3))}^2}} \\\\r = \sqrt {{{( - 5)}^2} + {{(4.583)}^2}} \\\\r = \sqrt {25 + 21} \\\\r = \sqrt {46} \end{array}\][/tex]

equation of the circle 1 is:

x² + y² = r²

(x - h)² + (y - k)² = r²

(x - 3)² + (y + 3)² = 46

Equation for Circle 2

where Focus(-7, -3) of a hyperbola is the center of a circle

Center(-7, -3) and passes through the farther vertex of a hyperbola (-2, -7.583)

[tex]\[\begin{array}{l}r = \sqrt {{{({x_2} - {x_1})}^2} + {{({y_2} - {y_1})}^2}} \\\\r = \sqrt {{{( - 2 - ( - 7))}^2} + {{( - 7.583 - ( - 3))}^2}} \\\\r = \sqrt {{{(5)}^2} + {{( - 4.583)}^2}} \\\\r = \sqrt {25 + 21} \\\\r = \sqrt {46} \end{array}\][/tex]

equation of the circle 2 is:

x² + y² = r²

(x - h)² + (y - k)² = r²

(x +7)² + (y + 3)² = 46

Answer:

Equation of Circle 1

(x - 3)² + (y + 3)² = 46

Equation of Circle 2

(x + 7)² + (y + 3)² = 46

Problem 3:

y² + 12x +6y = 39

(y - k)² = 4a(x - h)

y² + 6y + 3² = 39 - 12x + 3²

(y + 3)² = 48 - 12x

(y + 3)² = -12(x - 4)

V(h, k)

V(4, -3)

4a = -12

a = -3

Vertex of parabola is the vertex of the hyperbola

V(4, -3)

X = x + 4

X = 3 + 4

directrix: x = 7

conjugate axis of the hyperbola is on the directrix of a parabola

Conjugate axis which is at

Center (7, - 3)

Focus(a , 0)

X = x - 4 ; Y = y + 3

x = X + 4 ; y = Y - 3

x = -3 + 4 = 2 ; y = 0 - 3 = -3

Focus (1, -3)

Focus of parabola is the foci of the hyperbola

Focus (1, -3)

Equation of hyperbola

[tex]\[\frac{{{{(x - h)}^2}}}{a^2} - \frac{{{{(y - k)}^2}}}{b^2} = 1\][/tex]

h = 7

k = -3

a = 3

b = √27

c = 6

Answer:

[tex]\[\frac{{{{(x - 7)}^2}}}{9} - \frac{{{{(y + 3)}^2}}}{{27}} = 1\][/tex]

#CarryOnLearning